Comparative Transcriptome Analysis Of Rubber Tree (Hevea Brasiliensis) Between High And Low Yield Rubber Clones Related To Natural Rubber Biosynthesis - Abu Bakar, Mohd Fahmi (2020)
This study is focussing on gaining some knowledge and important information related to genes that control natural rubber production. The knowledges are related to biosynthesis pathways involved, relationships of the tissues and expression of genes related to natural rubber production which is very important for development of high yield rubber clone through rubber breeding program.